Advancing environmental sustainability through nature-based science tourism: The potential of universities - Räikkönen Juulia; Rouhiainen Henna; Grénman Miia; Sääksjärvi Ilari E. (Suomen matkailututkimuksen seura, 2022)
This review examines the potential of universities to advance environmental sustainability through nature-based science tourism, in which scientists are actively involved in co-creating nature-based tourism experiences. We first justify the review by presenting the current changes facing academia, namely the pressure to increase societal effectiveness, science democratization, and environmental sustainability. Then, we define science tourism and address the role of science and scientists in nature-based tourism. Finally, we evaluate the potential of nature-based science tourism to affect tourists’ environmental knowledge, atitudes and behavior. Based on previous literature, we suggest that universities and scientists, who have the knowledge about environmental sustainability, biodiversity crisis, and climate change, could have a more significant role in providing nature-based tourism experiences and shaping tourists’ attitudes and behavior regarding environmental sustainability. In line with recent discussions on science dissemination, this requires not only providing scientific knowledge to large audiences but also active scientific engagement and interaction with tourists.